Party system under occupation : a case study of Palestine, 1987-2011 - Shobaki, Belal M. M. (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study examines and analyzes the Palestinian party system after the establishment of Hamas movement, within the period 1987 -2011. Most of the data required to analyze and examine the Palestinian party system was obtained from the government and party documents in addition to personal interviews. Because the Palestinian party system operates within two internal and external environments, the researcher used the System Theory of David Easton so as to analyse the internal and external factors affecting the Palestinian party system. After discussing the emergence of the most important Palestinian parties, their thoughts and development, the researcher moved to identify the most important elements of the internal and external environments, where the impact of media, civil society, clans, the Israeli occupation and the foreign interference on the Palestinian party system were examined. It was found that the internal environment of the Palestinian party system was affected by the parties more than they affect it, while the external environment played an influential role on the party relations. In order to understand the Palestinian party system, the emergence of these parties and the most important characteristics of the Palestinian party system like pluralism, competitiveness and the absence of the party law were examined. Moreover, both environments led to the instability of the party system in particular and the political system in general. The governments were not stable and the first experience of the government alliances failed. The final result was a political and security conflict that affected the Palestinian social and economic structure negatively.